Characterization of CwlC, an autolysin, and its role in mother cell lysis of Bacillus thuringiensis subsp. israelensis. (1st January 2022) - Huang, L.; Xu, L.; Han, G.; Crickmore, N.; Song, F.; Xu, J.
Abstract: Bacillus thuringiensis subsp. israelensis ( Bti ) has been proven to efficiently control mosquitoes, of which many species are important vectors of human disease. The larvicidal action is attributed to the parasporal crystals formed in the sporulating cells and released upon cell autolysis. In this study, a sporulation‐specific cwlC gene that encodes an N ‐acetylmuramoyl‐L ‐alanine amidase was characterized in Bti strain Bt‐59. CwlC was the only cell wall hydrolase in Bti found to contain both Mur N Ac‐LAA and Amidase02_C domains. A recombinant CwlC‐His protein was able to digest the Bacillus cell wall. Deletion of the cwlC gene delayed Bti mother cell lysis without impacting vegetative growth or insecticidal efficacy. Transcriptional analyses indicated that cwlC was expressed at the late sporulation stage and was controlled by SigK. Two other cell wall hydrolase genes, cwlB and cwlE, with high expression levels at T 14 in Bt‐59, were also identified. Like cwlC, cwlB expression was controlled by SigK; in contrast, cwlE was found not to be under the control of this sigma factor and unlike the other two, its gene was found to be plasmid encoded.